Immobilisation of Candida rugosa lipase on aminated polyethylene/polypropylene microfibrous sheet modifieded with oxirane group - Akbar Tajudin, Hazimah; Al-Khatib, Ma'an Fahmi Rashid; Mirghani, Mohamed Elwathig Saeed; Mohd. Salleh, Hamzah; Nasef, Mohamed Mahmoud (The Academy of Sciences Malaysia, 2018)
An active microfibrous substrate containing aminated brush obtained by radiation-induced grafting of glycidyl methacrylate (GMA) onto a polyethylene/polypropylene (PE/PP) microfibrous sheet followed by amination reaction was prepared and used for immobilisation of Candida rugosa lipase under various conditions. The aminated microfibrous sheet was characterised by Fourier-transform infrared spectroscopy (FTIR-ATR) and field emission scanning electron microscope (FESEM). The amine group density on the aminated micro-fibrous sheet was found to be 3.33mmol/g. Response surface methodology (RSM) was applied to model and optimise the immobilisation conditions including immobilisation time (2-6 h), medium pH (pH 7-9) and enzyme/support ratio (5.0-9.0mg/cm2). The model generated from RSM was significantly correlated with the studied parameters for the residual activity of the immobilised lipase. The optimum values for immobilisation time, medium pH, and enzyme/support ratio were found to be 4.24h, pH 8, and 8.51mg/cm2 respectively. The enzymatic activity using p-nitrophenyl palmitate (pNPP) as substrate was 1.4588U/cm2 under optimum conditions. The pH endurance, storage, and thermal stability of the immobilised lipase were remarkably enhanced. The immobilised lipase can be readily recovered and more than 50% of its activity was retained following 10 cycles. The results of this study suggested that the aminated microfibrous sheet of PE/PP grafted with poly(GMA) is a promising polymer support for enzyme immobilisation with high potential for broad biocatalytic applications.